PLM-based approach for Assembly Process Engineering. (6th October 2010) - Demoly, Frederic; Gomes, Samuel; Eynard, Benoit; Rivest, Louis
The paper presents a methodology in the field of Design for Assembly (DFA) related to the Assembly Process Engineering (APE) and the Product Lifecycle Management (PLM). This method has been designed to develop assembly methods into a legacy web-based PLM prototype. It takes into consideration assembly constraints in the early phases of the product development process in compliance with concurrent engineering challenge. A racing car ground-link system from an experimental case study is introduced to illustrate the proposed approach.